Cuestiones de método creativo: Metamorfosis y conciencia material en los procesos creativos en arquitectura (2014)
By inquiring in the art of poetry, phenomenology and studies on technological making, this article attempts to bring creative processes in architecture closer to its imaginative essence. It presents questions of creative method following a discursive sequence whose demonstrative hypothesis departs from the idea that making architecture is place-making, whether it is: built, electronically mediated or “paper architecture.” The article demonstrates that the concepts of place and poetry are analogous, by bridging from the literary and phenomenological fields. Processes of poetic imagination (metaphor and metamorphosis) subsequently are explored and exemplified with architectural works, grouped in three categories according to distinctive ways in which material imagination makes presence as metamorphosis. Developing this study required building a theoretical frame from a hermeneutic interpretative situation specific to architecture, and then applying the resulting conceptual construct to the analysis of architectural works, drawing demonstrative conclusions